CORRELATION ANALYSIS AMONG FOREIGN LANGUAGE ANXIETY, READING ANXIETY, AND READING ACHIEVEMENT OF STUDENTS OF PUBLIC HEALTH FACULTY OF SRIWIJAYA UNIVERSITY - HESTI WAHYUNI ANGGRAINI (Sriwijaya University Learning and Education International Conference, 2016)
The objectives of this research are to (1) to determine whether there is a significant correlation between the level of students’ anxiety in the foreign language and the ability to read text in foreign language; (2) to know whether there is a significant correlation between the students’ level of anxiety in the foreign language reading and the ability to read text in foreign language, and (3) to find out whether there is a significant correlation among students’ level of anxiety in the foreign language and anxiety in the ability to read text in foreign language and students’ reading ability of Faculty of Public Health students Sriwijaya University.This research is a correlational study. The samples of this research are the 240 students of English Education Study Program chosen purposively. The data were gathered by using 2 ready-made questionnaires and TOEFL Reading Section test. The results of this research showed that (a) there was no correlation between students’ foreign language anxiety level and reading achievement as shown in Pearson Correlation 0.046 and R-square 0.002; (b) there was statistically correlation between students’ reading anxiety level and reading achievement as shown in Pearson Correlation 0.196 and R-square 0.038; and (3) students’ foreign language anxiety level and students’ reading anxiety level were statistically correlated, as shown in Pearson Correlation 0.199 and R-square 0.04.